Hot Water-Treated Cow Waste Use as an Efficient Adsorbent for Cresol Red Dye and Chromium VI Removal from Aqueous Solutions - Ali El-Rayyes; Ibrahim Arogundade; Abimbola Aina Ogundiran; Mohamed Hefnawy; Edwin Andrew Ofudje; Ali El Gamal; Lamia A. Albedair; Amnah Mohammed Alsuhaibani (BioResources)
Hot water-treated cow waste (HWTCW) was used as an efficient, low-cost, and sustainable adsorbent for the removal of cresol red dye and chromium(VI) from aqueous solutions. Functional groups present on the biomass surface were identified by Fourier Transform Infrared Spectroscopy as -OH, C=O, C=C, and C-O. The scanning electron microscopy analysis showed the structure relating to plant tissue and rough surfaces that were heterogeneous and irregular, revealing the origin of the biomass to be cellulose, lignin, hemicellulose, and other water-soluble components. Maximum adsorption capacity was attained at biomass dosage of 40 and 50 mg, 120 and 140 min as the time of contact, pH of 4 and 3, and temperature of 40 and 45 °C for CR and Cr (VI) adsorption. The equilibrium data from the adsorption of CR and Cr (VI) followed Langmuir and Freundlich models with maximum uptake of 73.3 and 66.4 mg/g. For the adsorption of CR by HWTCW, a pseudo-first-order kinetic model provided a better fit, whereas a pseudo-second-order model provided a better fit for Cr (VI) ions adsorption. The analysis of ΔH gave positive values of 22.4 kJ/mol for CR and 46.0 kJ/mol for Cr (VI) indicating the endothermic process.